Branding Furniture Workshop Rangawak Barulak Tanah Datar Karya Akhir - Fajar Novario Zulvianda; San Ahdi (Universitas Katolik Widya Karya Malang, 2023)
Rangawak is a wood-working workshop in Barulak, Tanah Datar that produces hand-processed products without using massive manufacturing machines. Rangawak has been running since 2019, by utilizing the surrounding wood resources which are designed and processed to produce valuable furniture. However, this is still not enough to make Rangawak a sustainable brand. Rangawak needs more than just a quality product, but also a strong brand image, so it is easily recognized by potential consumers. Branding steps are deemed appropriate to overcome this problem using the design thinking method which focuses on empathy, defining problem, ideation and refining solutions. This method includes experimentation, development of ideas in visual form and physical implementation based on existing problems. The branding process results in the design of ideal branding elements, compiled into a brand book so that it becomes a reference for acting both internally and externally. These elements are in the form of values held firmly by the brand, brand positioning in the market, calm explanation of brand naming, brand personality which becomes a reference for how the brand interacts (in the form of tone of voice, prohibited and recommended terms, pronunciation and choice of words in copywriting), as well as visual identity with guidelines and rules for its application in various supporting media such as websites, catalog books, posters, member cards, packaging and Instagram accounts selected based on indicators of the media's effectiveness and efficiency in the brand activation process.